Vaccinia Neutralization Test Using a Radioisotope Assay for Virus-induced Enzyme Activity - Ziegler, Donald W. (1969)
Vaccinia virus induction of a metabolic activity in host cell cultures forms the basis of a new assay for neutralizing antibodies. A direct relationship between the amount of vaccinia virus infecting cell cultures and the induced incorporation of tritium-labeled thymidine into the acid-insoluble fraction of the cells provided an indicator system. A liquid scintillation spectrometer was used to determine radioactivity associated with cell materials, and it provided a method for partial automation of an immunological procedure. Reproducibility of the method was satisfactory, and agreement with conventional vaccinia serum neutralization tests was demonstrated.